Human side of change : a practical guide to organization redesign - Galpin, Timothy J. (Jossey-Bass Pub. San FranciscoUS, 1996)
Presents a pragmatic approach for dealing with the human aspects of organizational change. Provides a change process model, as well as tools, techniques, examples and tool kits for use by change managers. Addresses issues including: the use of team infrastructure to accomplish the change process; communication fundamentals in the change process; and, provision of feedback and coaching during the change process.